Ecosystem service multifunctionality of Chinese fir plantations differing in stand age and implications for sustainable management - Zeng, Yelin; Wu, Huili; Ouyang, Shuai; Chen, Liang; Fang, Xi; Peng, Changhui; Liu, Shirong; Xiao, Wenfa; Xiang, Wenhua (Science of The Total Environment, 2021)

The impact of secondary forest restoration on multiple ecosystem services and their trade-offs - Zeng, Yelin; Gou, Mengmeng; Ouyang, Shuai; Chen, Liang; Fang, Xi; Zhao, Lijuan; Li, Jiaxiang; Peng, Changhui; Xiang, Wenhua (Ecological Indicators, 2019)

rTRIPLEXCWFlux: An R package for carbon–water coupling model to simulate net ecosystem productivity and evapotranspiration in forests - Sun, Shulan; Ouyang, Shuai; Hu, Yanting; Zhao, Zhonghui; Liu, Meixian; Chen, Liang; Zeng, Yelin; Peng, Changhui; Zhou, Xiaolu; Xiang, Wenhua (Environmental Modelling & Software, 2023)

Linkage between tree species richness and soil microbial diversity improves phosphorus bioavailability - Wu, Huili; Xiang, Wenhua; Ouyang, Shuai; Forrester, David I.; Zhou, Bo; Chen, Lingxiu; Ge, Tida; Lei, Pifeng; Chen, Liang; Zeng, Yelin; Song, Xinzhang; Peñuelas, Josep; et al. (Functional Ecology, 2019)
Abstract Increased availability of soil phosphorus (P) has recently been recognised as an underlying driving factor for the positive relationship between plant diversity and ecosystem function. The effects of plant diversity on the bioavailable forms of P involved in biologically mediated rhizospheric processes and how the link between plant and soil microbial diversity facilitates soil P bioavailability, however, remain poorly understood. This study quantified four forms of bioavailable P (CaCl 2 ‐P, citric‐P, enzyme‐P and HCl‐P) in mature subtropical forests using a novel biologically based approach, which emulates how rhizospheric processes influence the release and supply of available P. Soil microbial diversity was measured by Illumina high‐throughput sequencing. Our results suggest that tree species richness significantly affects soil microbial diversity ( p < 0.05), increases litter decomposition, fine‐root biomass and length and soil organic carbon and thus increases the four forms of bioavailable P. A structural equation model that links plants, soil microbes and P forms indicated that soil bacterial and fungal diversity play dominant roles in mediating the effects of tree species richness on soil P bioavailability. An increase in the biodiversity of plants, soil bacteria and fungi could maintain soil P bioavailability and alleviate soil P limitations. Our results imply that biodiversity strengthens plant and soil feedback and increases P recycling. A plain language summary is available for this article.

Plant functional trait diversity and structural diversity co-underpin ecosystem multifunctionality in subtropical forests - Ouyang, Shuai; Gou, Mengmeng; Lei, Pifeng; Liu, Yue; Chen, Liang; Deng, Xiangwen; Zhao, Zhonghui; Zeng, Yelin; Hu, Yanting; Peng, Changhui; Xiang, Wenhua (Forest Ecosystems, 2023)

Tree growth rate and soil nutrient status determine the shift in nutrient-use strategy of Chinese fir plantations along a chronosequence - Wu, Huili; Xiang, Wenhua; Ouyang, Shuai; Xiao, Wenfa; Li, Shenggong; Chen, Liang; Lei, Pifeng; Deng, Xiangwen; Zeng, Yelin; Zeng, Lixiong; Peng, Changhui (Forest Ecology and Management, 2020)

A Numerical Study of the June 2013 Flood-Producing Extreme Rainstorm over Southern Alberta - Li, Yanping; Szeto, Kit; Stewart, Ronald E.; Thériault, Julie M.; Chen, Liang; Kochtubajda, Bohdan; Liu, Anthony; Boodoo, Sudesh; Goodson, Ron; Mooney, Curtis; Kurkute, Sopan (Journal of Hydrometeorology, 2017)
Abstract A devastating, flood-producing rainstorm occurred over southern Alberta, Canada, from 19 to 22 June 2013. The long-lived, heavy rainfall event was a result of complex interplays between topographic, synoptic, and convective processes that rendered an accurate simulation of this event a challenging task. In this study, the Weather Research and Forecasting (WRF) Model was used to simulate this event and was validated against several observation datasets. Both the timing and location of the model precipitation agree closely with the observations, indicating that the WRF Model is capable of reproducing this type of severe event. Sensitivity tests with different microphysics schemes were conducted and evaluated using equitable threat and bias frequency scores. The WRF double-moment 6-class microphysics scheme (WDM6) generally performed better when compared with other schemes. The application of a conventional convective/stratiform separation algorithm shows that convective activity was dominant during the early stages, then evolved into predominantly stratiform precipitation later in the event. The HYSPLIT back-trajectory analysis and regional water budget assessments using WRF simulation output suggest that the moisture for the precipitation was mainly from recycling antecedent soil moisture through evaporation and evapotranspiration over the Canadian Prairies and the U.S. Great Plains. This analysis also shows that a small fraction of the moisture can be traced back to the northeastern Pacific, and direct uptake from the Gulf of Mexico was not a significant source in this event.

Photosynthetic and hydraulic traits influence forest resistance and resilience to drought stress across different biomes - Hu, Yanting; Xiang, Wenhua; Schäfer, Karina V.R.; Lei, Pifeng; Deng, Xiangwen; Forrester, David I.; Fang, Xi; Zeng, Yelin; Ouyang, Shuai; Chen, Liang; Peng, Changhui (Science of The Total Environment, 2022)

Stand carbon storage and net primary production in China’s subtropical secondary forests are predicted to increase by 2060 - Jin, Jia; Xiang, Wenhua; Zeng, Yelin; Ouyang, Shuai; Zhou, Xiaolu; Hu, Yanting; Zhao, Zhonghui; Chen, Liang; Lei, Pifeng; Deng, Xiangwen; Wang, Hui; Liu, Shirong; et al. (Carbon Balance and Management, 2022)
Abstract Background Forest ecosystems play an important role in carbon sequestration, climate change mitigation, and achieving China's target to become carbon (C) neutral by 2060. However, changes in C storage and net primary production (NPP) in natural secondary forests stemming from tree growth and future climate change have not yet been investigated in subtropical areas in China. Here, we used data from 290 inventory plots in four secondary forests [evergreen broad-leaved forest (EBF), deciduous and evergreen broad-leaved mixed forest (DEF), deciduous broad-leaved forest (DBF), and coniferous and broad-leaved mixed forest (CDF)] at different restoration stages and run a hybrid model (TRIPLEX 1.6) to predict changes in stand carbon storage and NPP under two future climate change scenarios (RCP4.5 and RCP8.5). Results The runs of the hybrid model calibrated and validated by using the data from the inventory plots suggest significant increase in the carbon storage by 2060 under the current climate conditions, and even higher increase under the RCP4.5 and RCP8.5 climate change scenarios. In contrast to the carbon storage, the simulated EBF and DEF NPP declines slightly over the period from 2014 to 2060. Conclusions The obtained results lead to conclusion that proper management of China’s subtropical secondary forests could be considered as one of the steps towards achieving China’s target to become carbon neutral by 2060.

Stability in subtropical forests: The role of tree species diversity, stand structure, environmental and socio‐economic conditions - Ouyang, Shuai; Xiang, Wenhua; Gou, Mengmeng; Chen, Liang; Lei, Pifeng; Xiao, Wenfa; Deng, Xiangwen; Zeng, Lixiong; Li, Jiangrong; Zhang, Tao; Peng, Changhui; Forrester, David I. (Global Ecology and Biogeography, 2021)
Abstract Aim Tree species diversity can increase the stability of ecosystem productivity by increasing mean productivity and/or reducing the standard deviation in productivity. However, stand structure, environmental and socio‐economic conditions influence plant diversity and might strongly influence the relationships between diversity and stability in natural forest communities. The relative importance of these factors for community stability remains poorly understood in complex (species‐rich) subtropical forests. Location Subtropical area of southern China. Time period 1999–2014. Major taxa studied Forest trees. Methods We conducted bivariate analyses to examine the mechanisms (overyielding and species asynchrony) underlying the effects of diversity on stability. Multiple regression models were then used to determine the relative importance of tree species diversity, stand structure, socio‐economic factors and environmental conditions on stability. Structural equation modelling was used to disentangle how these variables directly and/or indirectly affect forest stability. Results Tree species richness exerted a positive effect on stability through overyielding and species asynchrony, and this effect was stronger in mountainous forests than in hilly forests. Species richness positively affected the mean productivity, whereas species asynchrony negatively affected the variability in productivity, hence increasing forest stability. Structural diversity also had a positive effect, whereas population density had a negative effect on stability. Precipitation variability and slope mainly had indirect influences on stability through their effects on tree species richness. Main conclusions Overall, tree species diversity governed stability; however, stand structure, socio‐economic conditions and environmental conditions also played an important role in shaping stability in these forests. Our work highlights the importance of regulating stand structure and socio‐economic factors in forest management and biodiversity conservation, to maintain and enhance their stability to provide ecosystem services in the face of unprecedented anthropogenic activities and global climate change.

Effects of stand age, richness and density on productivity in subtropical forests in China - Ouyang, Shuai; Xiang, Wenhua; Wang, Xiangping; Xiao, Wenfa; Chen, Liang; Li, Shenggong; Sun, Han; Deng, Xiangwen; Forrester, David I.; Zeng, Lixiong; Lei, Pifeng; Lei, Xiangdong; et al. (Journal of Ecology, 2019)
Abstract Forest productivity may be determined not only by biodiversity but also by environmental factors and stand structure attributes. However, the relative importance of these factors in determining productivity is still controversial for subtropical forests. Based on a large dataset from 600 permanent forest inventory plots across subtropical China, we examined the relationship between biodiversity and forest productivity and tested whether stand structural attributes (stand density in terms of trees per ha, age and tree size) and environmental factors (climate and site conditions) had larger effects on productivity. Furthermore, we quantified the relative importance of environmental factors, stand structure and diversity in determining forest productivity. Diversity, together with stand structure and site conditions, regulated the variability in forest productivity. The relationship between diversity and forest productivity did not vary along environmental gradients. Stand density and age were more important modulators of forest productivity than diversity. Synthesis . Diversity had significant and positive effects on productivity in species‐rich subtropical forests, but the effects of stand density and age were also important. Our work highlights that while biodiversity conservation is often important, the regulation of stand structure can be even more important to maintain high productivity in subtropical forests.